PECULIARITIES OF TRANSLATING FRENCH PHRASEOLOGICAL UNITS OF POLITICAL DISCOURSE INTO UKRAINIAN (Based on the Speeches of Modern French Politicians) - Nesterova, Olga (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The article is devoted to the peculiarities of the translation of modern French idioms of political discourse into Ukrainian. A theoretical study of methods of transmitting idioms in the Ukrainian language was conducted. The research revealed four ways of translating idioms: complete phraseological equivalent, phraseological analogue, tracing and descriptive translation. The translation of idioms based on the speech material of modern French political figures is analyzed to identify more appropriate methods of translating phraseological expressions for political discourse._______________References:• Alefirenko F. (2004) Frazeologizm. Ukrainska mova; Encyclopedia. (Kyiv: Ukrainska encyclopedia imeni M. P. Bajana).URL: http://litopys.org.ua/ukrmova/um210.htm• AlievaA.D., KoostykE.V. (2023).«Osoblyvostiperekladuangliyskyhidiom». Nova fìlologìâ: 9–14.• HolotukO. V. (2018). «Osoblyvostiperekladufrancuzkyhfrazeologiszmivfrancuzkoumovou». NaukovyivisnykHersonskohoderjavnohouniversytetu. Vol. 2. Iss 34: 216–220.• Osoblyvostiperekladufrazeologizmivzukrainskoimovyangliyskoyu (2021). Ujhorod : P.P. Danylo: С.І. 104 с.• SerаjymK. S. (2001). «Leksykatafrazeologiapolitychnohodyskursu». NaukovizapyskyInstytutuJurnalistyky. Vol. 5: 70–72.• CherednychenkoО. І. (2001). «Frazeologiasuchasnohopolitychnohodyskursu». VisnykKyivskohonatsionalnohouniversytetuimeniTarasaSchevchenka. Inozemna filologia. Vol. 31: 5–7.• Chetaikina V. (2024). «Functions of idioms in political discourse». Scientific Journal of Polonia University.Vol. 64. No. 3: 16–22.• Crif - Discours du Premier ministre Gabriel Attal à l'occasion du 38ème Dîner du Crif. URL: https://www.crif.org/fr/content/crif-discours-du-premier-ministre-gabriel-attal-a-loccasion-du-38eme-diner-du-crif• Déclaration de politique générale de M. Gabriel Attal, Premier ministre, sur les grandes orientations de la politique gouvernementale notamment en matière d'industrialisation, de santé, d'éducation, de sécurité et d'agriculture, à l'Assemblée nationale le 30 janvier 2024. URL: https://www.vie-publique.fr/discours/292847-declaration-de-politique-generale-gabriel-attal• Dictionnaire des expressions françaises. URL: https://www.expressio.fr/• Discours de Marine Le Pen au Congrès du Front National à Lille. URL: https://rassemblementnational.fr/discours/discours-de-marine-le-pen-au-congres-du-front-national-a-lille• Discours du Président Emmanuel Macron à l’Assemblée générale des Nations unies. URL: https://onu.delegfrance.org/discours-du-president-emmanuel-macron-a-l-assemblee-generale-des-nations-unies• Gramely,, Patzold, K-M. (1992). A Survey of Modern English. New York: Routledge.• Macron aux médaillés de Tokyo: "mettre les bouchées doubles" pour les JO de Paris 2024. URL: orange.fr/videos/plus-de-sport/jo-ete/macron-aux-medailles-de-tokyo-mettre-les-bouchees-doubles-pour-les-jo-de-paris-2024-CNT000001ElJ0R.html• Seidl, J., & McMordie, W. (1978). English Idioms and How to Use Them. Oxford University Press.• Le dictionnaire libre. URL: https://fr.wiktionary.org/wiki/Wiktionnaire: Page_d%E2%80%99accueil.
Keywords: phraseology, idiom, political discourse, phraseological equivalent, phraseological analogue, tracing, descriptive translation